Protection of the Gender-Based Violence Victims in the European Union - Román Martín, Laura; Freixes Sanjuán, Teresa (Universitat Rovira i Virgili, 2014)
In this publication the preliminary results are presented of the European Epogender project Gender violence: protocols for the protection of victims and effectiveness of protection orders. Towards and efficient implementation of Directive 2011/99/EU, carried out under the Daphne III Programme (2007-2013) of the European Union. The handbook focuses on the analysis of the national legislation of the EU Member States regarding protection measures for the victims of gender violence, as well as the issues that may arise in applying the European protection order.